ANALISIS PERBANDINGAN KUALITAS SINYAL KONEKTIVITAS GSM DAN LORA PADA GPS TRACKER - Riyanjaya, Ahmad Fadli; Muttaqin, Adharul; Purnomowati, Endah Budi (Jurnal Mahasiswa TEUB, 2023)
The emergence of a new signal transmission protocol is a consideration in choosing the type of connectivity to be used, especially on a GPS Tracker. This study aims to develop a design of GPS Tracker testing stages using GSM and LoRa connectivity and determine the value of Packet loss in sending data using GSM and LoRa connectivity on a GPS Tracker. This research includes Research and Development research that uses experimental techniques. The results of the analysis of data communication and GPS Tracker LoRa signal reception resulted in an average packet loss value of 10%, RSSI of -116 dBm, and SNR of 0.2 dB. The analysis of data communication and GPS Tracker GSM signal reception results in an average packet loss value of 0%, RSSI of -65 dBm, and SNR of 23 dB. GSM connectivity has better quality in Non-Line of Sight (NLOS) test conditions in urban areas than LoRa connectivity. The performance and distance between the LoRa gateway transmitter and BTS with receiver (GPS Tracker) have a high influence on the quality of data communication and signal reception. The farther the transmitter is from the receiver, the worse the quality of data communication and signal reception, and vice versa. Keywords: Connectivity, GSM, LoRa, GPS Tracker